(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
On the basis of performed literature overview and analysis of the effect of production modes on physical indices of fibreboards, following variable factors were determined: pressing temperature, board thickness and binder content. In this paper, the results of the performed analytical and empirical investigations with respect to the effect of pressing temperature, board thickness and binder content on physical properties of MDF-type boards (medium-density fibreboards manufactured after the dry method) made of hard hardwood species are presented. Regression models showing the effect of variable factors on board indices were derived. The changes in the values of those indices in case of combinations of levels of production factors were examined. Analysis of the result was made, with the respective conclusions having been drawn.